MGNREGA: A Paradigm Shift in Employment and Income Generation in Meghalaya - Dkhar, D. S.; Tripathi, A. K.; Roy, A.; Feroze, S. M.; Saravanan, R.; Singh, N. U. (Indian Journal of Hill Farming, 2017)
The National Rural Employment Guarantee Scheme (NREGS) came into existence after an enactment of the Parliament Act ‘National Rural Employment Guarantee Act’ (2005) in September 2005 and immediately it started functioning in Meghalaya too. A study has been conducted in East Khasi Hills District of Meghalaya to see the impact of the programme on Livelihood improvement of rural households. It was observed that there was 27.43 per cent increase in the income of beneficiaries after joining in MGNREGA approved activities. The beneficiaries have realized 19.66 per cent higher income as compared to that of non-beneficiaries in the study area. It was also found that, average monthly expenditure on food and non-food items of beneficiaries have increased by 5.20 per cent and 14.23 per cent respectively after working in MGNREGA. The average monthly expenditure of beneficiaries on food items has increased 12.72 per cent and similar result was also found in non-food items where the expenditure increased 21.19 per cent as compared to that of non- beneficiaries.